Comparison of the efficacy of expandable interbody fusion cage (EXP-IFC) and non-expandable interbody fusion cage (NE-IFC) in MIS-TLIF for lumbar degenerative diseases: A systematic retrospective study on 62 patients - Chen, Chen; Li, Qiang; Wang, Wei; Ji, Chunlei; Kang, Yi; Wang, Chaoyu; Zhang, Hongyi; Zhang, Ming; Zhou, Hengxing; Feng, Haoyu; Feng, Shiqing (Frontiers in Surgery, 2022)
Objectives To investigate the clinical and radiographic outcomes of EXP-IFC in single-level MIS-TLIF. Methods This study included patients aged ≥18 years who received a single-level MIS-TLIF procedure with at least 1 year of follow-up. Outcome measures: clinical features, preoperative and neurological complications. Imaging analysis included disc height (DH) restoration, surgical and contralateral side foraminal height (FH), lumbar lordosis angle (LL), segmental lordosis (SL). Visual analog scale (VAS) score for low back pain (VAS-LBP) and leg pain (VAS-LP), Oswestry Disability Index (ODI) and Japanese Orthopaedic Association (JOA) score were used to evaluate clinical outcomes. Statistical analysis was performed using independent sample t-test and sample t-test. The significance was set to p < 0.05 in univariate analysis. Results A total of 62 patients undergoing single level MIS-TLIFs between January 2017 and January 2019 were included, with 32 NE-IFC 46.9% female, mean age 54.86 ± 11.65, mean body mass index (BMI) 24.59 ± 3.63) and 30 EXP (40% female, mean age 58.32 ± 12.99, mean BMI 24.45 ± 2.76) with no significant differences in demographics. There were no significant differences between two groups in Operative time (OT), Estimated blood loss (EBL) and Length of stay (LOS). No significant differences were found in VAS-LBP, VAS-LP, JOA and ODI in post-operation and the last follow-up between the two groups. The imaging outcome demonstrated that the mean increase in DH was significantly greater for the patients with EXP-IFC than those with NE-IFC group at 1 year follow-up (8.92 ± 0.51 mm EXP-IFC vs. 7.96 ± 0.96 mm NE-IFC, p < 0.001). The mean change in FH of operative and contralateral sides were observed to be significantly higher for the patients with EXP-IFC at 1 year follow-up (operative side:17.67 ± 2.29 mm EXP-IFC vs. 16.01 ± 2.73 mm NE-IFC, p = 0.042; contralateral side:17.32 ± 2.26 mm EXP-IFC vs. 16.10 ± 2.32 mm NE-IFC, p < 0.001), but changes in LL and SL were not significantly different. At the last follow-up, we did not find any significant difference in the fusion rate between the two groups. Conclusion Our results indicated that there may be no significant difference in short-term clinical outcomes between EXP-IFC and NE-IFC, but the use of EXP-IFC in MIS-TLIF can provide a significant restoration of disc height, and neural foraminal height compared to NE-IFC.